Data Mining on the Crawl Frontier: Metaphor in Cybernetic Capitalism - Timothy Erik Ström (Law Text Culture, 2022)
This essay explores how the intangible operations of networked computing-machines are frequently described through tangible metaphors. After looking at their origins in military bureaucracies, this analysis steps through the material operations of Google’s famous search-engine, noting the various metaphors that are used to make sense of it, and the way they frequently draw on colonial and extractive imagery. I give an account of the company’s rise to power, emphasising how their immense profits became possible because of their control of intellectual property rights, as well as over the ‘terms and conditions’. Across this critical analysis, I show how these metaphors embody the dominant worldview of cybernetic capitalism and demonstrate how they serve as ways to cope with the extreme abstractions increasingly enmesh us.